Blockchain for record-keeping and data verifying: proof of concept - Ghazali, R. (Springer, 2021)
The paper aims to show how blockchain, particularly Ethereum private blockchain, performs as a record keeper for Malaysian Muslim marriage records as a case study. The study also aims to demonstrate how blockchain technology conserves marriage data and improves data sharing efficiency involves accessing data from the blockchain and multiple users through proof of concept (POC). This POC also intended to seek evidence of immutability, transparency, and authenticity claims by the technology to ensure the record's security is a high priority. The study implements a smart contract on the Ethereum platform in the Government of Malaysia network environment and, the results provide significant evidence of private Ethereum blockchain principles of high availability, efficiency, immutability, transparency, and truthfulness particularly in record keeping. Future research can investigate other blockchain technology for other blockchain initiatives, such as blockchain disruptors. This paper is useful for management researchers and guides management practice for decision-making when determining whether the technology can use as a record-keeper. This paper proposes POC to design and develop record-keeping of Malaysian Muslim marriage records using Ethereum blockchain technology. Â© 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.